Targeting light versus deep sedation for patients receiving mechanical ventilation - Boncyk, Christina; Nahrwold, Daniel A.; Hughes, Christopher G. (Journal of Emergency and Critical Care Medicine; Vol 2 (October 2018): Journal of Emergency and Critical Care Medicine, 2018)
Each year, millions of patients within intensive care units (ICUs) across the world are exposed to invasive monitors, procedures, devices, and mechanical ventilation as part of their treatment that necessitates analgesia and sedation for associated pain and anxiety (1,2). As clinicians, we aim to support healing while minimizing the discomfort these diagnostic procedures or therapies frequently evoke. To this end, sedation is commonplace within the ICU.